REHABILITASI MAKNA KERUKUNAN ANTAR UMAT BERAGAMA (REFLEKSI ATAS NILAI-NILAI QUR’ANI) - Lufaefi, Lufaefi (Khazanah: Jurnal Studi Islam dan Humaniora, 2017)
Diversity is a fact that is often denied by some who do not want to be responsible, so often assume others who disagree and not the same as himself as the culprit of mistakes, and he is the most correct among others. They forget the history of the plurality of the country. This has actually hurt the already grounded culture in the archipelago that this nation was born into a culture of diversity. Unfortunately, the person who is reluctant to take responsibility often makes the verses of the Quran justify his behavior. Consequently, the moral spiritual of Qur'an is often politicized for the benefit of the individual, or even his group by putting aside the cultural heritage mentioned above. Yet the essence of holy revelation [al-Quran] always tells us to uphold the truth in diversity culture. The culture of multiculturalism is indeed embodied and legalized in the spiritual of Qur'an. This is in accordance with the mission of the Koran itself as a revelation that saalih likulli time wa al-meal that has long confirmed the legality of difference and diversity.